Kolaborasi Tripusat Pendidikan Dalam Pengembangan Karakter Islami - ahmad syukron; syafruddin syafruddin; muhammad azhari (Fakultas Pendidikan IAI Pangeran Dharma Indramayu, 2025)
This research aims to develop a tripartite collaboration model of education involving family, school, and community in reinforcing Islamic character among students. Utilizing a qualitative approach and case studies on two Madrasah Aliyah in Bekasi Regency, five synergy models with varying effectiveness were identified, with the integrative-systematic model proving to be the most effective. The analysis results indicate that three-way communication, program connectivity, and value consistency are key to the success of Islamic character education. Local cultural factors and the utilization of digital technology also influence the implementation of this model. These findings recommend the importance of structured and sustainable collaboration to create a generation that is characterized, virtue and ready to face the challenges of the times.